Accuracy of queries for storage space optimisation in green data centre - Rabatul Aduni, Sulaiman (2014)
Proxy based approach is the technique that can be used to make sure the storage space of the database can be minimized towards the development of the green data centre. The idea of proxy based technique is via the schema modification of datasets by dropping some attribute under functional dependency relationships. When the attribute is dropped from the table, it can cause the information loss and can make the query process error. But, when the droppable attribute can be retrieved by using another table, the problem can be solved. Another table in this situation is referred to the proxy map table. The query is needed in the retrieval process. But, it needs to make sure that the query is more simple and able to retrieve the data. The query transformation is another technique that can help proxy based to minimize the storage space. Query transformation will make sure the data can be retrieve successfully. Accuracy of queries help to analyze the result of query transformation and compare with result before query transformation is applied. The result of an attributes selection, query process and the comparison of storage space will be shown in this project. This project will be concluded with the basic characteristic of the proxy map that can help to minimize the storage space and contribute in the development of green data centre.